Perbaikan Alat Pengukus dan Pengemasan Jumbrek untuk Meningkatkan Produktifitas dan Kualitas: Improvement of Jumbrek Steaming and Packaging Equipment to Increase Productivity and Quality - Ismawati, Rita; Muhaji, Muhaji; Romadhoni, Ita Fatkhur (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Jumbrek is a traditional semi-moist cake from Paciran, Lamongan Regency, East Java. This traditional snack is made from a mixture of rice flour, coconut milk, and siwalan palm sugar syrup, combined in specific proportions and then stirred until homogeneous. The mixture is poured into trumpet-shaped molds made from siwalan leaves and steamed. Currently, the steaming process utilizes a pot equipped with a bamboo steamer. The existing equipment has several drawbacks: the steaming time is lengthy, the volume capacity is limited due to steam leakage from the loosely sealed lid, and the steamer is not sturdy. Repeated use causes the bamboo weave to deteriorate, leading to a risk of collapse. In addition to the inadequate steaming apparatus, another issue is the packaging, which consists of thin plastic that tears easily and lacks visual appeal. The implementation of this project involved several stages, including surveys, observations, interviews, collaboration with jumbrek-producing small and medium enterprises (SMEs), equipment design, manufacturing, assembly, functional testing, equipment delivery, guidance, and the application of new tools and product packaging. The outcomes of the project include a jumbrek steamer that meets the requirements of the SMEs, characterized by robust construction, practicality, increased strength, and improved hygiene. The new steamer can accommodate 140 units of jumbrek in 45 minutes, representing a three- to fourfold increase in productivity compared to the previous steamer, and enhanced packaging, consisting of durable, transparent, and aesthetically appealing bags made from thick plastic, measuring 30 cm by 32 cm, with an attractive design and labeling.